Espesor de capa de células ganglionares y capa de fibras del nervio óptico asociados a glaucoma en población menor a 18 años (2022)
Glaucoma is an optic neuropathy and the leading cause of irreversible blindness worldwide, in most cases it occurs in patients older than 60 years and also represents 5% of blindness in the population under 18 years of age at world (1). The diagnosis of glaucoma in Colombia corresponds to 0.08% of the total care for all causes of visual loss in the country, with a estimated prevalence for women of 0.15% in 2018, higher than that of men men (10). One of the structures that are most affected by glaucoma is the nerve. optic, which can suffer damage generally produced by a Pressure Intraocular (IOP) elevated. Sometimes there may be no symptoms except for a gradual loss of peripheral vision, which manifests itself in advanced states. Because it is a hereditary disease, professionals recommended if you have a family history, keep a check periodic IOP and in addition to the eye fundus evaluation, observing the coloration, vascularization and diameter of the optic disc, for a diagnosis and timely treatment (6) Within the characteristics of this disease we find the loss of of the nerve fiber layer of the retina, which leads to a decreased visual field and in advanced stages can lead to blindness. The atrophy that develops in glaucoma of any type is characterized by progressive loss of ganglion cells, histopathological disc alteration optic manifesting with increased papillary cupping, sequential deterioration of the visual field due to the loss of ganglion cells (1). two Ganglion cells process visual information that begins when light enters the eye and is transmitted to the brain, the axons of these cells make up the nerve fiber layer of the optic nerve. There are approximately 1 million ganglion cells in the human eye, which decrease during life approximately 25%. The focus of the disease is oriented in establish a timely diagnosis and effective treatment. One of the most commonly used tools is optical coherence tomography (OCT) used in daily practice both in the adult population and in the pediatric population, without However, for its correct interpretation we must take into account that the values of reference for the different thicknesses of the ocular structures are not the same in children and adults (4). OCT is a non-invasive, quick and painless imaging test that provides very precise and valuable information in the diagnosis and monitoring of different optic neuropathies. The latest devices in OCT contain a base of data extracted from populations carried out in adults, which limits its application in children and as a consequence no reference values ​​are available for children and adolescents under 18 years of age. For this reason, OCT requires a base of normative data for pediatric population for decision making essential in clinical practice (3).